A comparative histological analysis of human pulp following direct pulp capping with propolis or biodentine - Nehad A Ahmad; Nevin A Gad; Marwa H Abdulmonaem (Wolters Kluwer Medknow Publications, 2022)
Introduction: Pulp exposure in permanent teeth conventionally has been treated with calcium hydroxide pulp capping. The purpose of this study was to evaluate the histological finding of healthy human pulp tissue after pulp capping using new materials, Biodentine (BD) and Propolis (Pr). Materials and Methods: Forty intact human premolars scheduled for extraction for orthodontic reasons were mechanically exposed. Teeth were divided into four groups of ten teeth each and capped with Pr and BD. The final restoration was done with glass ionomer restorative material. The teeth were then extracted on the 15th or the 45th day and subjected to processing for histological evaluation by an image analysis software. Results: Differences in inflammatory response and dentine bridge formation of the exposed pulp to the different materials. The BD group, at all evaluation periods, exhibited a thick newly formed reparative bridge of dentin that totally obliterating the site of exposure. At the exposure site, cell inclusions and mineralization, variable numbers of odontoblast-like cells, preserved pulp tissue, marked numerous collagen fibers, and blood vessels, were observed. On the other hand, the Pr group did not show any presence of dentin bridge or calcified material and intermediate to acute inflammation after the 15th day. On the 45th day, Pr showed an entire newly formed bridge of reparative dentin tissue, complete pulp degeneration with multiple edematous spaces, hyperemic blood vessels, vacuolated odontoblasts, extravasated red blood cells, multiple mineralized structures dispersed just underneath the dentin bridge and through the pulp tissue, and newly ill-defined odontoblasts. Conclusion: For pulp capping, BD has a better dentin bridge formation and pulp preservation than pr in the human teeth.